Using Reader’s Theatre Strategy in Learning English Poetry: How Effective it Could be? - Irene Elena Khing (Journal of English Education and Teaching, 2020)
The purpose of this study was to investigate whether using Reader’s Theatre starategy could improve students’ comprehension level or not and exore students’ perception about the imlementation of Reader’s Theatre in learning English poetry. A total of eight participants from the same program in Kolej University Islam Perlis (KUIPs), Perlis were involved in the research. This study used Embedded Mixed Method in which preexperimental research was conducted in the quantitative stage of data collection, where the quantitative data were gained from students’ pre-test and posttest. Meanwhile the qulitative data were gained from the interview conducted at the end of experimental study. The data collected from the results of students’ pretest and posttest were analyzed by using paired samle T-Test, while thematic analysis was used to analyse the responses from interviews. The results of the analysis showed that 1) Reader’s Theatre strategy was able to enhance students’ comprehension level and 2) students showed positive perception that the learning activities with the implementation of Reader’s Theatre strategy brought three benefits; first, the activity was interesting and enjoyable, secondly, the activity made it easy to comprehend English literatures and thirdly, the activity made students work collaborativey in groups.